Structure and dynamics of G-quadruplex DNA studied by ensemble and single-molecule techniques - Sengar, Anjali (2017)
G-rich DNA sequences have a propensity to fold into four-stranded G-quadruplex structures. As G-quadruplexes are highly polymorphic structures understanding and manipulation of structural features offer great possibilities in the field of structural biology, medicinal chemistry and nanotechnology. This thesis explores the G-quadruplex formation in different sequence contexts. Two novel intramolecular G-quadruplex structures formed by biologically relevant poly-G tracts of 15 and 22 continuous guanines are presented. Another structural study has been carried out to investigate the G-quadruplex structure in the G-rich promoter sequence of the DNA repair protein PARP-1, showing three-layered, (3+1) hybrid G-quadruplex scaffold which could serve as a potential target for anti-cancer therapy. Structural dynamics of parallel G-quadruplexes and effect of loop length and inosine substitution on it have been studied using both ensemble and single molecule FRET techniques. Insights obtained from both ensemble as well as single molecule techniques contribute towards the understanding of G-quadruplex structures and dynamics.